Acute compartment syndrome as the initial manifestation of chronic-phase chronic myeloid leukemia: a case report and review of the literature. (December 2016) - Nagase, Yoshikazu; Ueda, Shuji; Matsunaga, Hitomi; Yoshioka, Aya; Okada, Yoshiyuki; Machida, Tomohisa; Nakata, Keiichi; Mima, Fuka; Takeda, Risato; Hayashi, Daisuke; Iio, Sadaharu; Okita, Kohei; et al.
Abstract Background Acute compartment syndrome is an orthopedic emergency requiring urgent fasciotomy to prevent irreversible damage. In hematological malignancies, acute compartment syndrome caused by severe soft tissue bleeding is extremely rare. We present a patient with chronic-phase chronic myeloid leukemia who had acute compartment syndrome caused by severe soft tissue bleeding in her right forearm. Case presentation A 72-year-old Japanese woman was referred to our hospital with swelling and pain of her right forearm without a previous history of trauma. She was diagnosed with chronic-phase chronic myeloid leukemia. Extreme thrombocytosis was present, although no evidence of acquired von Willebrand disorder was found. Compartment syndrome caused by soft tissue bleeding was confirmed. An emergency fasciotomy for decompression was conducted. However, sustained postoperative bleeding occurred and required massive red cell concentrate transfusion. As her platelet count decreased by cytoreductive therapy, complete hemostasis was achieved. Conclusions Patients with an extremely high platelet count might be at high risk for severe bleeding complications even without acquired von Willebrand disease. For the control of severe bleeding complications in patients with myeloproliferative disorder, the importance of thrombocyte reduction should be recognized.